2017
DOI: 10.1007/s13246-017-0590-y
|View full text |Cite
|
Sign up to set email alerts
|

A survey of modulated radiotherapy use in Australia & New Zealand in 2015

Abstract: A survey of radiation oncology medical physics departments across Australia and New Zealand was conducted to assess the usage, commissioning and quality assurance of modulated radiotherapy techniques such as IMRT and VMAT. Survey responses were collected in April-May 2015 to snapshot current practice and historical implementation. The survey asked 142 questions, and is the most detailed survey of its kind published to date. Analysis of results at overall department level, as well as sub-analysis for different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The most common form of PSQA involves the comparison of TPS dose calculations with 2D or 3D dose measurements . The gamma evaluation method (also known as gamma analysis, or gamma index analysis), developed by Low et al is widely used to compare such measurements .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common form of PSQA involves the comparison of TPS dose calculations with 2D or 3D dose measurements . The gamma evaluation method (also known as gamma analysis, or gamma index analysis), developed by Low et al is widely used to compare such measurements .…”
Section: Introductionmentioning
confidence: 99%
“…%GP can be used by the users to establish or apply action levels. Surveys of PSQA practices have reported that ∆D and DTA criteria of 3%/3 mm are the most frequently used …”
Section: Introductionmentioning
confidence: 99%
“…The 3% ΔD criterion was selected in this study because it is widely used, in combination with a range of Δd values, but the use of 3% as a ΔD criterion is not universal. Similarly, GAI values of 100% and 95% were selected as examples of extreme and commonly‐used PSQA action levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The ΔD of 3% was chosen for this work because it is very widely recommended and used. Recent surveys suggested that 3%/3 mm are currently the most commonly used gamma evaluation criteria, and the AAPM's task group report on IMRT commissioning (TG‐119) used 3%/3 mm and the AAPM's more recent task group report on modulated radiotherapy quality assurance (TG‐218) recommended 3%/2 mm. Investigations of cranial and extra‐cranial stereotactic radiotherapy have reported the use of 3%/2 mm, 3%/1.5 mm, 3%/1 mm and 3%/0.3 mm criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation